Negotiating Merariq: Cultural Continuity and State Efforts to Prevent Child Marriage in East Lombok - Apriansyah, Joli; Evi Satispi; Taewoo Park; Muhammad Sahrul; Bariyah, Oneng Nurul (Universitas Andalas, 2025)
This study examines the role of the East Lombok government and Muhammadiyah in addressing child marriage within the Sasak community, with particular attention to the culturally embedded practice of Merariq. Conducted over two months of fieldwork between January and February 2025, the research employed a qualitative design that combined document analysis, participatory observation, and in-depth interviews with ten local community members, two religious leaders, and five government officials. Data were analyzed using an iterative coding process beginning with open coding to identify emergent patterns, followed by focused coding aligned with Bourdieu’s framework supplemented by theoretical triangulation to enhance analytical rigor. The findings indicate that although legal frameworks have been formally implemented, their effectiveness is hindered by entrenched cultural norms, economic pressures, and the coexistence of overlapping legal systems. In contrast, Muhammadiyah’s initiatives, particularly its reinterpretation of Islamic values and its community-based family-strengthening programs, have demonstrated greater cultural resonance and have offered practical alternatives to early marriage. These insights underscore the necessity for culturally sensitive and multi-institutional approaches that effectively integrate statutory enforcement, religious authority, and community engagement. The study contributes to broader discussions on child marriage prevention by illustrating how tradition, law, and religion interact within pluralistic societies, and by providing actionable pathways for local institutions to reduce child marriage while honoring cultural heritage.